FACTORS SHAPING THE ADOPTION OF ARTIFICIAL INTELLIGENCE IN EDUCATION - Milutinovic, Verica; Djordjevic, Suzana; Obradovic, Ivana (Metodička teorija i praksa, 2025)
With the growing influence of Artificial Intelligence (AI) in education, this study explores the factors shaping the intention of future teachers and educators to integrate AI-based tools into their practices. It investigates how variables such as intelligent-ethical Technological Pedagogical Content Knowledge (TPACK), AI-related anxiety, subjective norms, AI for social good, and self-assessed AI competence influence this intention. Data were collected from 157 pre-service teachers at the Faculties of Education in Jagodina and Belgrade, and multiple regression analysis revealed that 72.9% of the variance in intention to use AI was explained by these variables. Intelligent-ethical TPACK (β = 0.501, p < 0.001) emerged as the strongest predictor, followed by AI for social good (β = 0.296, p < 0.001) and subjective norms (β = 0.195, p < 0.01). The results highlight the importance of enhancing teacher education programs to develop intelligent-ethical TPACK and awareness of AI’s role in promoting social good.